Tanzania's oil and gas contract regime, investments and markets - Peter Bofin; Rasmus Hundsbæk Pedersen (Danish Institute for International Studies (DIIS), 2017)
This paper analyses the development of Tanzania's petroleum sector based on a review of laws and contracts. It provides an overview of current upstream activities and discusses the potential for the commercialisation of finds through the increasingly important midstream contracts that govern the use of natural gas. It demonstrates that Tanzania has managed to build institutional capacity over the years, but that it struggles to keep abreast of market signals. As a frontier market it experiences a later surge in exploration activities by international oil companies when oil prices are high when compared to more developed markets. Furthermore, its overstretched institutions are also slow at reacting to such changes. The adjustment of its legal and institutional framework therefore often happens too late, potentially undermining the benefits the country could harvest from the sector. Currently, some adjustment may be needed to make it a driving force in the Tanzanian economy.
Keywords: 330